Religion and Scientific Culture in Learning Curriculum 2013 - Supriyono, Supriyono (CV. Creative Tugu Pena, 2022)
The purpose of this article was to analyze satinfitic religion and culture in 2013 curriculum learning. This research was literature, which documentation and observation in collecting the data. Primary data was obtained from reading reference books, journals, and websites. The findings of this study showed that Islamic education towards the process of integrating science and religion was relevant and beneficial for the scientific development of Islamic religious education in the future. A harmonious religious paradigm will make scientific creativity more developed and more relevant to play its role optimally. Religion requires science and science requires religion, so that its actualization produces beneficial values ??for human society in the world. It wa proven that the failed modernist paradigm with the buzz of reason was sufficient for the life of the world. In the realm of education, the implementation of learning in schools within the framework of the 2013 curriculum, shows a relevant offer to prepare Indonesia's golden generation in 2045. Keywords: Religion and Scientific Culture, Curriculum 2013, Scientfic Culture